2021
DOI: 10.1088/1757-899x/1090/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ACI code for predicting the flexural capacity and deflection of reinforced geopolymer concrete beams

Abstract: A conventional Portland cement can be considered as the most consumed energy material, since it isresponsible on about 1.35 billion tons annually, occupying is approximately 6% of global CO2 emissions. It can be stated that the emission related to CO2 is the main reason of global warming and greenhouse effect. For this reason, studies have been devoted to find a clean source of material to be an alternative for the traditional cement. Geopolymer concrete is being emerged as a promised construction material tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Alex et al [57] reported that GPC beams exhibited 9% greater midspan deflection than OPC beams. Zinkaah et al [22] also reported that midspan deflections of GPC beams were greater than OPC beams. The nominal moment capacity (đť‘€ đť‘› ) of shear reinforced beams expected to fail in flexure was computed using Equation (1).…”
Section: Applied Loads (P U ) and Midspan Deflections Of Opc And Gpc ...mentioning
confidence: 95%
See 2 more Smart Citations
“…Alex et al [57] reported that GPC beams exhibited 9% greater midspan deflection than OPC beams. Zinkaah et al [22] also reported that midspan deflections of GPC beams were greater than OPC beams. The nominal moment capacity (đť‘€ đť‘› ) of shear reinforced beams expected to fail in flexure was computed using Equation (1).…”
Section: Applied Loads (P U ) and Midspan Deflections Of Opc And Gpc ...mentioning
confidence: 95%
“…Alex et al [57] reported that GPC beams exhibited 9% greater midspan deflection than OPC beams. Zinkaah et al [22] also reported that midspan deflections of GPC beams were greater than OPC beams.…”
Section: Applied Loads (P U ) and Midspan Deflections Of Opc And Gpc ...mentioning
confidence: 95%
See 1 more Smart Citation
“…Another study for bending and deflection calculations evaluated the applicability of the ACI 318-2019 code for geopolymer concrete beams. It has been stated that a suitable model is needed to calculate the flexural strengths and deflections of geopolymer concrete beams after the first crack formation [30]. When adding glass fiber or steel fiber and hybrid propylene while manufacturing fly ash-based geopolymer-reinforced concrete beams, the bending capacity increased by 30-35% [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Alumina and silica undergo rapid reactions in an alkaline environment during polymerization, forming a three-dimensional network of polymeric chains [13,14]. Furthermore, the performance of GPC is greatly influenced by the type of activators employed and the availability of aluminosilicates [15]. Compared to conventional concrete, GPC exhibits significantly lower CO2 emissions, with reduction rates ranging from 9% [16] to over 80% [17].…”
Section: Introductionmentioning
confidence: 99%